TGF-β1-Mediated PD-L1 Glycosylation Contributes to Immune Escape via c-Jun/STT3A Pathway in Nasopharyngeal Carcinoma - Ma, Xue-Min; Luo, Yun-Fan; Zeng, Fang-Fang; Su, Chang; Liu, Xiong; Li, Xiang-Ping; Lu, Juan (Frontiers in Oncology, 2022)
Immunotherapy targeting programmed death ligand-1/programmed cell death protein-1 (PD-L1/PD-1) has achieved great success in multiple cancers, but only a small subset of patients showed clinical responses. Recent evidences have shown that post-translational modification of PD-L1 protein could regulate its protein stability and interaction with cognate receptor PD-1, thereby affecting anticancer immunotherapy in several solid tumors. However, the molecular mechanisms underlying how PD-1/PD-L1 expression is regulated still remain unclear in nasopharyngeal carcinoma (NPC). Here, we found N-glycosylation of PD-L1 in NPC cells and tissues. Mechanistically, we showed that STT3A transferred N-linked glycans to PD-L1, and TGF-β1 could positively regulate STT3A expression through activating c-Jun to bind to STT3A promoter. Functional assays showed that inhibition of TGF-β1 resulted in a decrease of glycosylated PD-L1 and enhanced cytotoxic T-cell function against NPC cells. Analysis of clinical specimens revealed that the expression of STT3A was positively correlated with TGF-β1 and c-Jun, and high STT3A expression was positively correlated with a more advanced clinical stage. Altogether, TGF-β1 activated c-Jun/STT3A signaling pathway to promote N-glycosylation of PD-L1, thus further facilitating immune evasion and reducing the efficacy of cancer immunotherapy. As such, all these data suggested that targeting TGF-β1 pathway might be a promising approach to enhance immune checkpoint blockade, and simultaneous blockade of PD-L1 and TGF-β1 pathways might elicit potent and superior antitumor activity relative to monotherapies.